Potential of Hydrogen Production Through Alkaline Water Electrolysis Using Solar Radiation Around Semarang - Widarningtyas Ruth Pranindia; Sulistyo; Widayat (E3S Web of Conferences, 2019)
Indonesian society’s dependence on fossil fuel and the minimum GHG emission reduction target of 11% for the energy sector, encourages the development of hydrogen as an eco-friendly renewable energy resource for transportation and industries sector. Electrolysis is one of technology for hydrogen production. Electrolysis technology that utilizes the sun as a generating source is a eco-friendly technology of hydrogen production. The solar intensity in Semarang is 5.49 kWh/m2/day so that is potensial to used for hydrogen production. Solar intensity measurements were carried out in 2 locations in Semarang that have different altitude using single and parallel monocrystalline solar modules with observation from 8am-4pm. The measurement results are used as data for calculated the flow rate and the volume of hydrogen that can be produced. The highest hydrogen volume can be produced in Marina for single and parallel panel are 2,099.93 ml/h and 4,199.86 ml/h that are both at 10am. The highest hydrogen volume can be produced in Tembalang for single and parallel panel are 2,693.39 ml/h at 1pm and 5,751.98 ml/h at 11am. The altitude level of location greatly influences the solar intensity for hydrogen production. Parallel panel can produce hydrogen approximately 2 times single panel.